Traumatic axonal injury, a clinical-pathological correlation - Davcheva, Natasha; Sivevski, Atanas; Basheska, Neli (Elsevier BV, 2017)
Traumatic axonal injury (TAI) is a distinct clinicopathological entity that can cause serious impairment of the brain function and can sometimes be found as a concrete cause of death. It has been discussed from the perspective of its biomechanical importance, and also from the standpoint of certain criteria for the pathological diagnosis of TAI. However, since the time when DAI (diffuse axonal injury) was initially described, there have been few, if any, discussions about the clinical-pathological correlation in TAI. This paper is an attempt to address this issue. For the purpose of certain pathological diagnoses of TAI, 63 cases with closed head injuries have been subjected to the complete forensic-neuropathological examination, involving immunohistochemistry with antibody against β-APP. In the diagnosis of TAI strict criteria have been followed. Then, retrograde analysis of the clinical parameters has been performed in order to determine some clinical-pathological correlation. The following two most reliable parameters of the impairment of the brain function have been analyzed: the impairment of the consciousness and the time of survival. Comparing the two groups, the one with TAI and the other without TAI, and using appropriate statistical evaluation, our results show that TAI is not a significant contributing factor to the lethal outcome in the early post injury period (24 h), but it is undoubtedly a contributing factor for the severe impairment of the brain function indicated through the status of the consciousness.
Keywords: Closed head injury; Diffuse axonal injury; Traumatic axonal injury; β-amyloid precursor protein